(untitled) (Journal of Engineering, 2025)
Taziz Al-Taziz irrigation pumping station, within Al-Muthanna Governorate, Iraq, was studied, aiming at investigating the performance of its stilling basin in reducing the energy of the water out of the discharge pipes outlet. The study relied on the results of the physical model of the basic design of the stilling basin and the use of ANSYS Fluent 21.0 software to simulate both the basic design and the as-built stilling basin. The physical model was constructed and studied by the Center for Studies and Engineering Designs of the Iraqi Ministry of Water Resources. Simulations showed the variation in velocity within the basic design of Taziz Al-Taziz pumping station to be 3.98 m/s to 0.209 m/s in the basin, with an average velocity at the beginning of the canal of 1.4 m/s. For that, as built Taziz Al-Taziz, the velocity results showed a variation of 3 m/s to 0.209 m/s within the basin with an average velocity of 1m/s at the beginning of the canal. By converting the physical model’s measured results to a prototype, the average velocity at the beginning of the canal is 1.28 m/s. The efficiency of the basic design stilling basin is 30.7%, while that for the as-built is 50.5 % and 36.7% for the physical model. This indicates the quality and efficiency of the as-built stilling basin in dispersing a significant percentage of water energy from the pipes. Moreover, it was found that no negative pressure is developed within the basins.